If f(x) = 3x – 1 and g(x) = x + 2, find (f – g)(x). w O A. 4x+1 O B. 2x-3 o c. 2x-1 O D. 3 – 2x IR Question If f(x) = 3x – 1 and g(x) = x + 2, find (f – g)(x). w O A. 4x+1 O B. 2x-3 o c. 2x-1 O D. 3 – 2x IR SUBMI in progress 0 Math Peyton 3 days 2021-10-11T15:21:37+00:00 2021-10-11T15:21:37+00:00 1 Answer 0

## Answers ( )

Known:f(x) = 3x – 1

g(x) = x + 2

Asked:(f – g)(x) = …?

Answer:(f – g)(x)

= (3x – 1) – (x + 2)

= (3x – x) (-1 + 2)

=

2x – 1So, (f – g)(x) equal to

2x–1(C)Hopeithelpfulanduseful:)